Developing E-Module Based on Socio-Scientific Issues to Improve Students Scientific Literacy - Dalaila, Isvana; Widiyaningrum, Priyantini; Saptono, Sigit (Journal of Innovative Science Education, 2022)
Program of literacy that is implemented in the school has yet to lead in science learning, this makes the students to be less conscious of the essence of science literacy in the everyday life of students. This study aims to analyze the validity, practicality and effectiveness of using e-Module based SSI in improving the scientific literacy of high school students. This research is research and development by adopting the ADDIE model. Sampling using purposive sampling method with a total of 57 students consisting of class XI IPA 1 and XI IPA 3 SMAN 1 Mayong Jepara. The results showed that the analysis of the validity of the development of e-Module according to the material experts and media obtained 85,71% and 94,64% with the criteria of very valid. The analysis of the practicality of the response of the students obtained a value of 3.25 with practical criteria, as well as on the response of the teacher values obtained 3,94 with the criteria very practical. Analysis of the effectiveness of the N-Gain value in the medium category and classical completeness XI IPA 1 obtained 85.18% and XI IPA 3 obtained 76.67%. Based on the results of the study, it can be concluded that the SSI-based e-Module material on the immune system developed is valid, practical and used in learning immune system materials and is effective in improving the scientific literacy skills of high school students.